2015
DOI: 10.1186/s13062-015-0076-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of the WRKY III gene family in populus, grape, arabidopsis and rice

Abstract: BackgroundWRKY III genes have significant functions in regulating plant development and resistance. In plant, WRKY gene family has been studied in many species, however, there still lack a comprehensive analysis of WRKY III genes in the woody plant species poplar, three representative lineages of flowering plant species are incorporated in most analyses: Arabidopsis (a model plant for annual herbaceous dicots), grape (one model plant for perennial dicots) and Oryza sativa (a model plant for monocots).ResultsIn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 54 publications
2
75
0
Order By: Relevance
“…In previous studies, microsynteny analysis of several plant species was performed to identify the location of homologous genes (Li et al, 2014; Lin et al, 2014; Wang et al, 2015; Cao et al, 2016b). In our research, microsynteny was investigated to infer the relationship of the GRF genes between eudicots (pear, Populus , grape and Arabidopsis ) and monocots (rice).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, microsynteny analysis of several plant species was performed to identify the location of homologous genes (Li et al, 2014; Lin et al, 2014; Wang et al, 2015; Cao et al, 2016b). In our research, microsynteny was investigated to infer the relationship of the GRF genes between eudicots (pear, Populus , grape and Arabidopsis ) and monocots (rice).…”
Section: Resultsmentioning
confidence: 99%
“…The variation in the number of group III WRKY genes was considered to be one of the causes of diversity of WRKY gene family size [52]. In C. canephora, five group III CcWRKY genes were fewer than S. lycopersicum, A. thaliana, G. max, and similar to V. vinifera and C. papaya (Figure 1).…”
Section: Phylogenetic Analysis Conserved Motifs and Structure Of Thmentioning
confidence: 99%
“…It has been reported that WRKY genes from group III play an important role in plant adaptation and evolution [23]. In order to explore how the WRKY group III gene family evolved, a phylogenetic tree of WRKY group III proteins from sunflower with two dicots (Arabidopsis, grape) and two monocots (rice, maize) was constructed, which divided the 17 group III HaWRKYs into three clades.…”
Section: Discussionmentioning
confidence: 99%
“…Profiles of HaWRKY genes under abiotic and biotic stress23 HaWRKY genes which were highly induced in different tissues of common sunflower (except in pollen) were selected to test the reactions of different WRKY genes to different abiotic stresses. response to PEG, among them HaWRKY22/29/74 were significantly downregulated only at high concentration of PEG.…”
mentioning
confidence: 99%